Self‐confidence of anglers in identification of freshwater sport fish. (22nd October 2014) - Chizinski, C. J.; Martin, D. R.; Pope, K. L.
Abstract Although several studies have focused on how well anglers identify species using replicas and pictures, there has been no study assessing the confidence that can be placed in angler's ability to identify recreationally important fish. Understanding factors associated with low self‐confidence will be useful in tailoring education programmes to improve self‐confidence in identifying common species. The purposes of this assessment were to quantify the confidence of recreational anglers to identify 13 commonly encountered warm water fish species and to relate self‐confidence to species availability and angler experience. Significant variation was observed in anglers self‐confidence among species and levels of self‐declared skill, with greater confidence associated with greater skill and with greater exposure. This study of angler self‐confidence strongly highlights the need for educational programmes that target lower skilled anglers and the importance of teaching all anglers about less common species, regardless of skill level.